2021
DOI: 10.1080/08830185.2021.1922685
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis vaccine BCG: the magical effect of the old vaccine in the fight against the COVID-19 pandemic

Abstract: Bacillus Calmette-Guérin (BCG) is a live attenuated M. bovis vaccine that was developed about 100 years ago by Albert Calmette and Camille Guérin. Many countries have been using the vaccine for decades against tuberculosis (TB). The World Health Organization (WHO) recommends a single dose of BCG for infants in TB endemic as well as leprosy high risk countries, and globally almost 130 million infants are vaccinated yearly. The role of BCG is well known in reducing neonatal and childhood d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 96 publications
0
35
0
Order By: Relevance
“…It has been reported that 5-10% of patients with LTBI will progress to aTB during their lifetime (Hauck et al, 2009;Chee et al, 2018;WHO, 2018). However, the risk is higher in immunocompromised individuals, such as in people living with human immunodeficiency virus (HIV), people with diabetes, people with coronavirus disease, infants, and young children (aged < 5 years) (Chee et al, 2018;Gong and Wu, 2020;WHO, 2020;Aspatwar et al, 2021). In 2019, the number of new TB cases in countries with high TB burdens accounted for 86.9% of the global number of new TB cases (WHO, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 5-10% of patients with LTBI will progress to aTB during their lifetime (Hauck et al, 2009;Chee et al, 2018;WHO, 2018). However, the risk is higher in immunocompromised individuals, such as in people living with human immunodeficiency virus (HIV), people with diabetes, people with coronavirus disease, infants, and young children (aged < 5 years) (Chee et al, 2018;Gong and Wu, 2020;WHO, 2020;Aspatwar et al, 2021). In 2019, the number of new TB cases in countries with high TB burdens accounted for 86.9% of the global number of new TB cases (WHO, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Literature specifically addressing the effectiveness of BCG at improving morbidity and mortality resulting from COVID-19 disease remains varied and sometimes inconsistent [ 75 ]. This area of investigation is rapidly emerging and has garnered a great deal of interest [ 76 , 77 , 78 ]. Here, we review studies specifically investigating the effects of BCG vaccination on COVID-19 spread, morbidity, and mortality, excluding papers that have not yet been peer reviewed ( Table 2 ).…”
Section: Bcg and Covid-19: A Strategy To Reduce The Public Health Burden Of Epidemic Respiratory Disease?mentioning
confidence: 99%
“…Besides, recovery rates from SARS-CoV2 infection are higher in those countries as well. Therefore, BCG vaccination seems a promising approach to overcome SARS-CoV2 pandemic with its benign nature to human health [104]. In silico studies, based on homology, revealed that BCG vaccination can trigger production of cross-reactive T cells against SARS-CoV2 [105] along with enhanced innate immunity [106].…”
Section: Conventional Childhood Vaccines Against Sars-cov2 Pandemicmentioning
confidence: 99%
“…Cross-reactive dendritic cells (i.e. inf-cDC2s) that priming type I INF dependent [114] CD4 + and CD8 + T cells activation [108]; Downregulation of proinflammatory cytokine production [127]; various antiviral cytokine production, enhanced IFN-γ production and associated TH1 cells differentiation [104].…”
Section: Bcg Vaccinationmentioning
confidence: 99%